The Implementation of Religious Moderation Values among Islamic Senior High School Students - Dewi Musliha; Hasbullah Hasbullah; Alpizar Alpizar (Jurnal Indonesia Studi Moderasi Beragama, 2025)
Background: Fostering religious moderation in youth is crucial for building tolerance and peace, with Islamic senior high schools playing a key role in shaping balanced religious values to prevent radicalism and promote unity. Objective: This study aims to examine the implementation of religious moderation values among Islamic senior high school students. Method: This research employs a field research approach using a qualitative descriptive method. The study was conducted at Madrasah Aliyah Nurul Mubtadiin in 2022. Data were collected through observation, interviews, and documentation. The data analysis process consisted of three stages: data reduction, data presentation, and verification. Data validity was ensured through triangulation. Results: The findings indicate that the implementation of religious moderation values among students at Madrasah Aliyah Nurul Mubtadiin is well-executed and has become a flagship program in the school. Conclusion: The successful application of religious moderation values contributes to shaping students into a moderate generation with a strong sense of nationalism, high tolerance, and a rejection of violence. Contribution: This study serves as a reference for educators and policymakers in understanding and promoting religious moderation in schools, ensuring the development of students with balanced religious perspectives and social harmony.